Optimizing Solar Power: The Impact of N719 Dye Concentration on DSSC Efficiency with TiO2 Nanoparticles - Hardani Hardani; Ho Soonmin; Khaerus Syahidi; Alpi Zaidah; Sulistiyana Sulistiyana; Alpiana Hidayatulloh; Ahmad Fudholi; Lily Maysari Angraini (Pandawa Institute, 2025)
Dye-sensitized solar cells (DSSC) are photoelectrochemical, alternative energy source devices that convert light energy into electricity. In this study, DSSC with various concentrations (0.1, 0.5, and 1.0 mM) of N719 dye have been successfully prepared using simple steps. The X-ray diffraction results of the TiO2 film showed that it is polycrystalline with an anatase phase (tetragonal system) having a crystallite size of about 20 nm. The absorbance spectrum of the TiO2 film and N719 dye at various concentrations was recorded by ultraviolet-visible (UV-Vis) spectrophotometer. The bandgap energy of the TiO2 film calculated by Tauc’s formula was 3.1 eV. The DSSC prepared using the N719 dye concentration of 1 mM achieved the highest conversion efficiency (η) of 0.298 %, respectively. Subsequently, the enhancement in efficiency was 86 % compared with the conversion efficiency of DSSC prepared with an N719 dye concentration of 0.1 and 0.5 mM.